Rasch Model Analysis: Teacher Commitment Indicators by Experts Judgment - Ibnu Asakir; Dian Hidayati (Universitas Ahmad Dahlan, 2022)
Teacher commitment is the key to success in educational institutions. The school needs to measure the teacher's commitment to improving the quality of the school. The purpose of this study was to model expert judgment in the reliabilities and validity tests of Teacher commitment instruments using the Rasch model. The study involving 12 experts was conducted using a survey by assessing 18 items. Experts (respondents) are asked to evaluate the consistency of each item to represent one part of the Teacher commitment instrument. Expert judgment results using Rasch model analysis show that the average value of the logit scale is higher than logit 0.0. It is understood that more answering experts agree across a variety of items. The value Cronbach alpha, measuring reliability, i.e., the interaction between the person and the item as a whole, is seen as a value of 0.99, which means excellent. Person reliability value is estimated at 0.89, and item reliability is estimated at 0.60, indicating that the consistency of respondents' answers is good. However, the quality of items in the infrastructure is poor. It shows 17 items recommended being used as instruments to measureTeacher commitment, while 11 items are advised to be repaired.